2021
DOI: 10.1155/2021/6644625
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Moxibustion-Induced Microcirculatory Responses between the Heart and Lung Meridians Assessed by Laser Doppler Flowmetry

Abstract: Objective. By comparing the differences in microcirculatory responses of the heart and lung meridians induced by moxibustion on these two meridians, respectively, this study aimed to investigate the specificity for site-to-site association on body surface between different meridians. Methods. Eighty healthy adults were enrolled and divided into the lung meridian intervention group and heart meridian intervention group in a ratio of 1 : 1. Three-channel laser Doppler flowmetry was used to monitor microcirculato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(38 reference statements)
1
0
0
Order By: Relevance
“…Meridians are likely to be three-dimensional channels of multiple structures that transmit substance, heat, and energy, thereby the thermal transport effect along the meridian direction is more significant than that along the nonmeridian direction. Second, previous studies by our team yielded similar results using other techniques (i.e., laser Doppler flowmeter), which demonstrated that the change of blood flow induced by moxibustion was generally more significant in the distal sites along the corresponding meridian than that in the closer sites of the other meridian (34). The level of skin blood flow is subject to both reflex thermoregulatory control and influences from the direct effects of skin temperature (35).…”
Section: Principal Findingssupporting
confidence: 63%
“…Meridians are likely to be three-dimensional channels of multiple structures that transmit substance, heat, and energy, thereby the thermal transport effect along the meridian direction is more significant than that along the nonmeridian direction. Second, previous studies by our team yielded similar results using other techniques (i.e., laser Doppler flowmeter), which demonstrated that the change of blood flow induced by moxibustion was generally more significant in the distal sites along the corresponding meridian than that in the closer sites of the other meridian (34). The level of skin blood flow is subject to both reflex thermoregulatory control and influences from the direct effects of skin temperature (35).…”
Section: Principal Findingssupporting
confidence: 63%